IPV6 malicious router detection and recovery / Ahmad Saifullah Ahmad Tarmize - Ahmad Tarmize, Ahmad Saifullah (2015)
The increasing number of devices in the Internet led an increasing demand of IP address for every device. IPv4 cannot solve this problem requiring IPv6 protocol to be introduced. With IPv6 protocol, it includes Neighbour Discovery Protocol (NDP) for automatic configuration IP address thus makes it easy to use compare to IPv4. Although NDP simplify the configuration process of IPv6, there are few downsides to NDP protocol which could lead network to fall for certain vulnerabilities such as Man in the Middle (MitM), Denial of Service (DoS) and also spoofing problem. One of common problem is malicious router attack which announces itself as default router in the network to run MitM. Previously, there are multiple mechanisms to encounter NDP problem such as SEcure Neighbour Discovery (SEND) and RA Guard/DHCPv6 Guard. However, this technique falls to resource exhaustion, bandwidth consumption, added overhead and expensive hardware. This paper try to design new technique of detecting malicious router attack happen in NDP and recover network from the attack the simple way.